Silicon dioxide (SiO2) nanoparticles affect the morphology, sporulation, mycotoxin production, and pathogenicity of Fusarium brachygibbosum infecting olive trees - Meryam Belhedi; Meryam Belhedi; Besma Sghaier-Hammami; Mario Masiello; Haythem Nafati; Stefania Somma; Lucia Gambacorta; Rached Salhi; Rached Salhi; Mouna Messaoud; Sonia Labidi; Antonio Moretti; et al. (Frontiers in Nanotechnology)
IntroductionThis study investigates the In Vitro antifungal activity of silicon dioxide nanoparticles (SiO2 NPs) against mycotoxigenic Fusarium brachygibbosum species, a fungus posing a significant threat to olive trees in Tunisia.MethodsTwo different doses of SiO2 NPs (100 and 200 mg kg -1 ) were used to evaluate its effect on fungal growth, mycotoxin production, and virulence capability of tested F. brachygibbosum strain.Results and DiscussionWhile mycelial growth was not influenced by SiO2 NPs, a notable increase in macroconidia sporulation was observed at the highest dose tested. Scanning electron microscopy revealed structural alterations in fungal hyphae treated with SiO2 NPs, including hyphal disorganization after the adherence of nanoparticles. Furthermore, SiO2 NPs influenced oxidative stress in Fusarium, with varying effects on hydrogen peroxide levels, total antioxidant activity, and total phenolic compounds, modulating the capability of the fungus to produce mycotoxins. Indeed, fusaric acid and 15-acetyldeoxynivalenol amounts decreased in presence of SiO2, while an increasing level of neosolaniol and diacetoxyscirpenol was observed. Pathogenicity tests on olive and sorghum leaves revealed a reduction of disease severity in SiO2 treated samples compared to untreated controls, showcasing the potential of SiO2 NPs as a sustainable alternative for managing Fusarium infections. These findings underline the potential use of SiO2 NPs as environmentally friendly and effective tool in integrated pest management strategies against F. brachygibbosum as well as other Fusarium species occurring on olive trees. Further research is warranted to optimize their application and understand their interactions with both the pathogen and the host plant.